Hamilton & Hardy's industrial toxicology - Harbison, Raymond D.
"This book provides comprehensive coverage of all aspects of industrial toxicology, employing a succinct chapter format that has become the hallmark for the previous editions of Hamilton & Hardy's Industrial Toxicology"--Provided by publisher.